Evaluation of pharmacotherapeutic treatment in young people with anxiety disorder during the pandemic (Research, Society and Development, 2021)
Anxiety Disorder has affected young people with social isolation, thus canceling out people's social lives, leading to an increase in anxiety crises. During epidemics, the number of people whose mental health is affected tends to be greater than the number of people with infections (ORNELL et al. 2020). According to the Ministry of Health of Brazil (2020), an event like this causes psychological and social disturbances that affect the coping capacity of the entire society, at varying levels of intensity and spread. The objective was to understand how young people are behaving with anxiety disorder in the face of the pandemic. This study referred to an integrative literature review of the quantitative explanatory type. It was hoped to understand how young people are behaving with anxiety disorder during the SARS-CoV-2 pandemic, as well as to answer what consequences the disease has brought and if there was an increase in cases, considering that young people have awareness of the improvement in the quality of life that pharmacotherapeutic treatment can provide.